Nutritive evaluation of pulse chunies available in India by rumen simulation technique (Rusitec) - SWAIN, PARTHA SARATHI; RAO, D SRINIVASA; NAGALAKSHMI, D; PARASHURAMULU, S; PRUSTY, SONALI; RAY, S; SRIDHAR, K (The Indian Journal of Animal Sciences, 2016)
Chunies of pulses viz. black gram (Vigna mungo, BGC), bengal gram (Cicer arietinum, BnGC), red gram (Cajanus cajan, RGC) and green gram (Vigna radiata, RGC) were analyzed for their proximate composition. Degradability of dry matter was studied by Rusitec method. The degradability after 48 h of incubation corroborated to the values obtained with standard method. BGC (206.57) and GGC (232.29) are good protein supplements (g/kg DM) and BnGC (406.87) and RGC (309.68) are high in fiber content (g/kg DM). After 48 h of incubation, IVDMD (%) varied significantly from 50.06 (RGC) to 77.81 (BGC). The gas production ranged from 630.00 (BGC) to 1685.00 (BnGC) ml. The effective degradability of DM was higher in BGC and GGC than other chunies. It was concluded that nutritive value of BGC and GGC were better compared to BnGC and RGC and may be a good protein source for ruminants.